RECEPTION OF CHEKHOV'S TRADITION BY RUSSIAN DRAMA IN THE END XX - BEGINING XXI CENTURIES - I. V. Kupreeva (Гуманитарные и юридические исследования)
Ther article substantiates the need for the identification of modern drama relative to the previous literary tradition as a special aesthetic phenomenon that is a catalyst for a fundamental renewal in the arts. The influence of a literary text by Anton Chekhov on the theatrical reality of the XX century is considered. Aesthetic polyphony of A. Chekhov's drama (drama and epic pairing, dominant realist writing, working out the principles of modernist drama, the use of art techniques of impressionism) is the main reason for continuous reference of contemporary theater to the heritage of the great writer. Special attention is paid to the reception -the transformation of A. Chekhov's poetics code in Russian «new new drama» abroad XX-XXI centuries at the level of semantic dominants of the text (the trivialization of death as a phenomenon of everyday life, a sense of extinction of life, turning into the illusory nature of existence), the organization of psychological world of the characters, becoming carriers of the collective unconscious, the specifics of conflict relations with the substantial, open character, genre conditionality.